Nursing care demand from elderly women - Fidecki, Wiesław; Wysokiński, Mariusz; Wrońska, Irena (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Background. The main aim of the nursing care taken of an elderly person is providing support and necessary help in such a way so as to keep them active and independent, which determines maintaining health, independence and dignity. A type of actions undertaken by a nurse primarily depends on a patient’s degree of independence in meeting their living needs as well as functional and mental state of their organism. Aim of the study. The work aimed at specifying nursing care demand from elderly women staying in their home environments in the eastern part of Poland. Material and methods. The research was administered among 77 elderly women staying in their home environments in lubelskie, podkarpackie and podlaskie voivodeships. The age of patients involved in the investigation ranged from 65 to 89. The research material was collected by means of the Nurses’ Observation Scale for Geriatric Patients. Results and conclusions. The group of elderly women undergoing the research proved to enjoy relatively high efficiency within the scope of their psychosocial and physical functioning and consequently exhibited rather insignificant care demand. A place of residence considerably affected nursing care demand among females undergoing the research.